Effective Methods to Assess Exposure to Violence and Victimization Among American Indian and Alaska Native Youth: The Tribal Youth Victimization Study (TYVS), United States, 2019 - Melton, Ada Pecos ([Verlag nicht ermittelbar], 2021)
The purpose of the Tribal Youth Victimization Study (TYVS) was to develop and test survey research methods to assess American Indian (AI) and Alaska Native (AN) youth exposure to violence and youth victimization and to identify the factors of the exposure to victimization and its impact. The American Indian Development Associates, (AIDA) LLC conducted the study in partnership with several tribal communities and organizations. The goal is to develop a research strategy and survey instrument for collecting information on the violence and victimization experiences of American Indian and Alaska Native youth in tribal communities and other settings throughout the country. The study purpose is to determine and pilot test the tools and methods for conducting a future national level study. The data will be used to guide survey development, protocols and administration in tribal and other settings. This study included five (5) required tasks that framed the approach, methods, approvals, and deliverables, divided into three stages focused on three distinct phases - instrumentation, cognitive testing, and pilot testing. Phase 1 focused on development of the survey and the methods for survey administration to be tested. No data was collected during Phase 1 and was exempted from IRB review by the University of Nevada Las Vegas Human Subjects Biomedical Review Board. Phase 2 focused on testing recruitment methods and cognitive testing of the draft survey instrument. Phase 3 focused on pilot test site recruitment, pilot testing a revised version of the survey instrument, testing of three modes of administration, and testing alternative approaches to incentives.